2008
DOI: 10.1177/0022022107313905
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Cultural Specificity of Approaches To Learning in Universities in Hong Kong and Sydney

Abstract: Western research has characterized approaches to learning for specific learning tasks as discrete deep and surface approaches, distinguished by whether the intention is to understand or memorize. A more appropriate classification scheme for Hong Kong research is a continuum between deep and surface poles. In this article, the authors examine whether this characterization applies also to the West. University students in Australia ( n = 1,146) and Hong Kong ( n = 1,266) complete the revised Study Process Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
71
2
15

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 34 publications
17
71
2
15
Order By: Relevance
“…The mentioned statement has been however widely interpreted as 'deep and surface approaches are mutually exclusive constructs' (Kember, 1996;Tormey, 2014;Watkins & Mboya, 1997;Xie, 2014). That gives rise to a debate and criticisms that might mainly be based on 'misinterpretations', given that Biggs and colleagues consider that the same student may flip from surface to deep approaches depending on his or her perceptions of the learning environments (Biggs et al, 2001;Leung et al, 2008). To avoid such misinterpretations, the current study deviated from Biggs et al's (2001) root, by deliberately omitting the use of constraints during confirmatory factor analysis.…”
Section: Descriptivesmentioning
confidence: 91%
See 3 more Smart Citations
“…The mentioned statement has been however widely interpreted as 'deep and surface approaches are mutually exclusive constructs' (Kember, 1996;Tormey, 2014;Watkins & Mboya, 1997;Xie, 2014). That gives rise to a debate and criticisms that might mainly be based on 'misinterpretations', given that Biggs and colleagues consider that the same student may flip from surface to deep approaches depending on his or her perceptions of the learning environments (Biggs et al, 2001;Leung et al, 2008). To avoid such misinterpretations, the current study deviated from Biggs et al's (2001) root, by deliberately omitting the use of constraints during confirmatory factor analysis.…”
Section: Descriptivesmentioning
confidence: 91%
“…The R-SPQ-2F was cross-culturally validated by Leung, Ginns, and Kember (2008). The aim of their study was to determine whether the same structure could be found in Western and Eastern contexts.…”
Section: Validation and Use Of Spq And R-spq-2f In Different Contextsmentioning
confidence: 99%
See 2 more Smart Citations
“…8 They have a relational nature and can vary according to learning context. [9][10][11] Hence, the purpose of this research is to compare the study skills and strategies of the medical students among medical colleges in South India.…”
Section: Introductionmentioning
confidence: 99%